2004
DOI: 10.1211/0022357023448
|View full text |Cite
|
Sign up to set email alerts
|

Ion-pairs of ibuprofen: increased membrane diffusion

Abstract: The purpose of the present study was to determine the influence of pH and ion-pairing on the permeation of ibuprofen across polydimethylsiloxane (PDMS) membrane. The solubility of ibuprofen sodium was determined at a range of pH values. Saturated solutions were then used to determine the influence of pH on diffusion across PDMS as a model membrane. The apparent partition coefficient of ibuprofen sodium between n-octanol and phosphate buffer at various pH values was also investigated. Organic salts of ibuprofen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 20 publications
4
46
0
1
Order By: Relevance
“…Transmembrane permeation of ibuprofen observed from this study was significantly lower than that reported for both the single and the combined study designs (Al-Saidan, 2004;Hadgraft, Whitefield, & Rosher, 2003). Several previous studies also showed that ionization of ibuprofen helped increase its ability to penetrate through the stratum corneum and into the system, a method not utilized in this study (Al-saidan, 2004;Sarveiya, Templeton, & Benson, 2004). Nevertheless, oxybenzone in the single-component samples did yield permeation data comparable to those observed from other studies (Gustavsson Gonzales et al, 2002;Pont et al, 2004;Wang et al, 2006).…”
Section: Resultssupporting
confidence: 67%
“…Transmembrane permeation of ibuprofen observed from this study was significantly lower than that reported for both the single and the combined study designs (Al-Saidan, 2004;Hadgraft, Whitefield, & Rosher, 2003). Several previous studies also showed that ionization of ibuprofen helped increase its ability to penetrate through the stratum corneum and into the system, a method not utilized in this study (Al-saidan, 2004;Sarveiya, Templeton, & Benson, 2004). Nevertheless, oxybenzone in the single-component samples did yield permeation data comparable to those observed from other studies (Gustavsson Gonzales et al, 2002;Pont et al, 2004;Wang et al, 2006).…”
Section: Resultssupporting
confidence: 67%
“…Ion pairing is likely to be facilitated by the charged organic components within the membrane rather than the aqueous phase counter-ions of low lipophilicity. Ion-pairing mechanisms facilitating permeation/partition were reported in previous literature (43)(44)(45). This mechanism could explain the variation in both P u and P 0 .…”
Section: Permeability-ph Profilesmentioning
confidence: 75%
“…Here is one example: in cosmetic applications complexation has improved the photostability of sunscreens (Scalia et al, 1998;Scalia et al, 1999) but its influence on skin penetration behaviour is a compromise. There is an increasing effect due to better solubility (Vollmer et al, 1994;Legendre et al, 1995) but a decreasing effect resulting from using molecules with large relative molar masses (equivalent to more than 1000 Da) (Sarveiya et al, 2004;Simeoni et al, 2004;Williams et al, 1998). A recent trend is the use of modified cyclodextrin molecules.…”
Section: Cyclodextrins In Textile Dyeing Processesmentioning
confidence: 99%